2019
DOI: 10.3390/ijms20133249
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the Profile of Circulating miRNAs after Single Bouts of Resistance Training with and without Blood Flow Restriction—A Three-Arm, Randomized Crossover Trial

Abstract: Background: The effects of blood flow restriction (training) may serve as a model of peripheral artery disease. In both conditions, circulating micro RNAs (miRNAs) are suggested to play a crucial role during exercise-induced arteriogenesis. We aimed to determine whether the profile of circulating miRNAs is altered after acute resistance training during blood flow restriction (BFR) as compared with unrestricted low- and high-volume training, and we hypothesized that miRNA that are relevant for arteriogenesis ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 47 publications
1
22
0
9
Order By: Relevance
“…Recently, miRNA has been found to be effective in all kinds of diseases, including cardiovascular diseases [6]. miR-195-5p has been proved to be down-regulated in coronary artery blood flow disorders in the past [7], which suggests that miR-195-5p may be effective in the development and progression of cardiovascular diseases. However, it is not clear whether miR-195-5p can affect cardiomyocyte apoptosis in HF.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, miRNA has been found to be effective in all kinds of diseases, including cardiovascular diseases [6]. miR-195-5p has been proved to be down-regulated in coronary artery blood flow disorders in the past [7], which suggests that miR-195-5p may be effective in the development and progression of cardiovascular diseases. However, it is not clear whether miR-195-5p can affect cardiomyocyte apoptosis in HF.…”
Section: Introductionmentioning
confidence: 99%
“…The hemodynamic stimuli amplified by BFR lead to an increased release of endothelial NO synthase, among other responses [71]. Additionally, recent studies have shown that a single bout of strength training under BFR leads to changes in the miRNA expression profile [72]. So far, the parameters in animal and human studies to determine the mechanisms have only been identified by invasive measures such as muscle biopsies and whole blood samples.…”
Section: Myostatinmentioning
confidence: 99%
“…In the literature, many clinical studies assessed circulating miRNA levels in peripheral blood for diagnosing, predicting, and monitoring human diseases (158)(159)(160)(161)(162)(163), including cardiac and vascular disease (CVD) (164)(165)(166)(167)(168)(169). For example, the combination of miR-34a-5p and fibrinogen levels have been reported as a useful tool in differentiating pre-thrombotic status in patients with stable coronary artery disease (165).…”
Section: Emerging Challenge Of Bench Studies For Early Detecting and mentioning
confidence: 99%